The art public a short history - Bätschmann, Oskar 1943- (Reaktion Books, 2023)
Although the idea of a collective audience for art – an ‘art public’ – is highly significant in the art world, this is the first book to enquire into the actual history of the art public. The book explores both written and pictorial evidence of its behaviour, and disentangles the connections between art production, the expectations of the audience and a work’s reception. Two aspects shape the narrative: first, the transformation of the audience from passive recipient to active agent; and second, the mockery of the audience by satirists such as George Cruikshank, Thomas Rowlandson, Honoré Daumier and many others. This sweeping account moves from the Greek artist Apelles to Leon Battista Alberti and Leonardo da Vinci, and from Oscar Wilde to film stars, art tourists and leading art museums and galleries worldwide.
Keywords: Public art / History